Konsep Dasar Epistemologi Pendidikan Multikultural Dalam Islam - Zainun Wafiqatun Niam (At-Tarbiyat, 2019)
Education as a means of developing human potential and the formation of a community order must be carried out with the principles of equality and justice. The principle is based on the inevitability that humans live within the sphere of difference. Islamic education as a way of forming human beings, upholds the value of justice as a consequence of one of its roles as khalifatullah on the face of the earth, which is to prosper the universe. One aspect of education that can deliver this goal is the view of multiculturalism in Islamic education. This paper is aimed at looking at the basic concepts of the epistemology of multicultural education in Islam, which ultimately can be implemented in the process of Islamic education. The method used in writing this article is the "literature review" on the concept of multiculturalism, the basis of the epistemology of multiculturalism and multicultural education in Islam. The results obtained from this study are that multicultural education emphasizes the aspects of harmony in learning practices. The values ​​of multiculturalism do not conflict with the values ​​of Islam, they can even lead to the achievement of the goals of Islamic education, namely forming a harmonious order in social life.